Framework for 3D data modeling and Web visualization of underground caves using open source tools - Silvestre, Ivo (2013)
Terrestrial Laser Scanning is a very useful technique for cave studies. This surveying method creates point clouds with high detail levels for 3D model generation, which is indeed useful for either reconstruction, geomorphological studies or virtual visits of caves. The present work generated a 3D model of a cave chamber and developed a framework for 3D data visualization on the Web. Identifying geomorphological structures is one of the goals of this project. The generated 3D-mesh represents the surface model of the cave chamber, which is important to study its geomorphological features. A topological structure of the 3D-mesh was implemented to get an efficient algorithm to help determining stalactites. The recognition and positioning of cave stalactites can provide information on hidden cave features responsible for cave geomorphology. The possibility to publish 3D data on the Web is of particular interest for the geospatial field. For this reason, it was decided to make the cave model available in the Web by developing a 3D graphical interface where users can navigate and interact with the threedimensional models of the cave. For this Web framework, X3D, WebGL and X3DOM were used. Such solution does not require any additional plug-ins or components.